Americanismo(s) no Uruguai: os olhares entecruzados dos intelectuais sobre a América Latina e os Estados unidos (1917-1969) - Mateus Favaro Reis (2008)
This thesis aims to analyze Emilio Frugoni, José G. Antuña and Carlos Quijano interpretations between Latin America and United States relationships in the XXth century. Since 1917 up to the sixties, these three uruguayan intellectuals approved or censored the Latin America and Pan American movements of integration, and contributed in a special way on americanism debate in Uruguay. Carlos Quijano criticized Pan America idea and by publicizing newspapers promoted the Latin America movement of integration. EmilioFrugoni was one of most important socialist intellectuals in Uruguay and, despite some initial disagreements, crossed his route with Carlos Quijano on proposing Latin American sovereign projects. On the contrary, José G. Antuña diverged with Emilio Frugoni and Carlos Quijano on shielding Pan America conception, articulating it to his conservative hispanism.